To rearrange the slope formula \( y = mx + b \) for the quantity of interest \( m \), we will isolate \( m \) on one side of the equation. Here are the steps:
-
Start with the original equation: \[ y = mx + b \]
-
Subtract \( b \) from both sides to isolate the term with \( m \): \[ y - b = mx \]
-
Now divide both sides by \( x \) to solve for \( m \): \[ \frac{y - b}{x} = m \]
-
Finally, we can rewrite the equation to put \( m \) first: \[ m = \frac{y - b}{x} \]
Thus, we have successfully rearranged the slope formula for \( m \): \[ m = \frac{y - b}{x} \]